Maternal genetic polymorphisms in the major mitotic checkpoint genes MAD1L1 and MAD2L1 associated with the risk of survival in abnormal chromosomal fetuses - Chan, Ying; Liu, Yize; Kong, Yamin; Xu, Weiming; Zeng, Xiaohong; Li, Haichun; Guo, Yan; Tang, Xinhua; Zhang, Jinman; Zhu, Baosheng (Frontiers in Genetics, 2023)
Abstract Background: The genetic etiology of fetal chromosome abnormality remains unknown, which bring about an enormous burden for patients, family, and society. The spindle assembly checkpoint (SAC) controls the normal procedure of chromosome disjunction and may take part in the process. Objective: The aim is to explore the association between polymorphisms of MAD1L1 rs1801368 and MAD2L1 rs1283639804 involving in SAC and the fetal chromosome abnormality. Methods: The case-control study collected 563 cases and 813 health controls to test the genotypes of MAD1L1rs1801368 and MAD2L1 rs1283639804 polymorphisms by polymerase chain reaction-Restrictive fragment length polymorphism methods (PCR-RFLP). Results: MAD1L1rs1801368 polymorphism was associated with fetal chromosome abnormality alone or combined to lower homocysteine (HCY) level (alone: Dominant：OR: 1.75, 95% CI: 1.19-2.57, p =0.005；CT vs. CC: OR=0.73, 95%CI:0.57-0.94, p=0.016; lower HCY: C vs. T: OR=0.74, 95%CI:0.57-0.95, p=0.02; Dominant: OR=1.75, 95%CI:0.79-1.92, p=0.005). No significant differences were found in other genetic models or subgroups (p＞0.05 respectively). MAD2L1 rs1283639804 polymorphism revealed sole genotype in the studied population. HCY significantly is associated to fetal chromosome abnormality in younger group (OR: 1.78, 95% CI: 1.28-2.47, p =0.001). Conclusions: The results implied that the polymorphism of MAD1L1rs1801368 maybe become the susceptibility factor to fetal chromosome abnormality alone or combined to lower HCY levels, but not MAD2L1 rs1283639804 polymorphism. And HCY significantly affect the fetal chromosome abnormality for younger women.